Experimental Investigation of a Jet and Vortex Actuator Using Particle Image Velocimetry - Cadirci, Sertac; Gunes, Hasan; Rist, Ulrich; Peters, Bernd (American Society of Mechanical Engineers, 2012)
The Jet and Vortex Actuator (JaVA) is a zero-net-mass flux device for active flow control. JaVA was investigated experimentally using flow visualization and Particle Image Velocimetry (PIV) measurements and tested in still water instead of air to be able to make real-time observations with naked eye at an actuator plate frequency of f = 1 Hz. It has been already published that typical JaVA induced flow regimes are angled and vertical jets, wall jets and vortex flows. The flow types depend on the governing parameters including actuator plate width, the amplitude and the frequency of the actuator and the mean position of the actuator plate due to the JaVA cavity. First, we carried out extensive flow visualizations in an effort to observe flow dynamics qualitatively and describe the effect of governing parameters on JaVA induced flows. Then, we carried out PIV experiments and obtained quantitative data. We present results using velocity and vorticity fields for different types of jet flows. The suction and blowing phases of the jet flows, and mean jet flow rate and the jet momentum flux are investigated in detail. The vertical jet is found to have the maximum mean flow rate as well as the maximum jet momentum flux.